2000
DOI: 10.1046/j.1471-4159.2000.0750225.x
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of Tyrosine Hydroxylase Phosphorylation in the Nigrostriatal and Mesolimbic Systems In Vivo

Abstract: Electrical stimulation of the medial forebrain bundle increases 32 P incorporation into striatal tyrosine hydroxylase (TH) at Ser 19 , Ser 31 , and Ser 40 . In the present studies, the effects of acute haloperidol and related drugs on sitespecific TH phosphorylation stoichiometry (PS) in the nigrostriatal and mesolimbic systems were determined by quantitative blot immunolabeling using phosphorylation statespecific antibodies. The striatum (Str), substantia nigra (SN), nucleus accumbens (NAc), and ventral tegme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(127 citation statements)
references
References 38 publications
8
113
1
Order By: Relevance
“…9A). The short-term effect of haloperidol on TH phosphorylation is in agreement with previous reports (Salvatore et al, 2000;Håkansson et al, 2004). Hence, because of the clear time-dependent response on haloperidol-induced Ser40 phosphorylation, the effect of retigabine was monitored 30 min after haloperidol administration.…”
Section: Retigabine Blocks Induction Of Th Phosphorylation In the Strsupporting
confidence: 90%
“…9A). The short-term effect of haloperidol on TH phosphorylation is in agreement with previous reports (Salvatore et al, 2000;Håkansson et al, 2004). Hence, because of the clear time-dependent response on haloperidol-induced Ser40 phosphorylation, the effect of retigabine was monitored 30 min after haloperidol administration.…”
Section: Retigabine Blocks Induction Of Th Phosphorylation In the Strsupporting
confidence: 90%
“…It has previously been shown that Ser-40 in TH is specifically phosphorylated by cAMP-dependent protein kinase (PKA) (25). Thus, TH Ser-40 phosphorylation can be used as a measure of cellular cAMP levels in noradrenergic neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Each blot was cut at the 77-kDa protein marker and blocked in 5% BSA. The bottom portion of each blot was incubated overnight at 4°C in 1:200 Ser-40P-TH antibody (25), and the top portion was incubated in 1:250 PYK2 antibody (Upstate Biotechnology, Lake Placid, NY). After washing with Tris-buffered saline͞0.1% Triton X-100, blots were incubated with peroxidase-labeled 1:2,000 anti-rabbit IgG (Vector Laboratories) for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…This may also explain the activation of TH observed when assays are performed on cell extracts, even when Ser19 seems to be the only site phosphorylated, while most groups find no effect on enzyme activity resulting from the phosphorylation of TH at Ser19 in vitro. Recently, it was reported that even low incorporation of phosphate into Ser40 was sufficient to increase the TH activity in vivo (Salvatore et al 2000). Thus, the increased TH activity found in chromaffin cells may originate from Ser40 phosphorylation rather than Ser19 or from the presence of 14-3-3 proteins.…”
Section: Dephosphorylation Of Ser19 By Pp2amentioning
confidence: 99%
“…Ser19, Ser31 and Ser40, by a variety of protein kinases, indicating that its regulation may involve multiple signalling pathways. Studies on TH from several species suggest that Ser40 is the main site involved in direct activation of TH (Sutherland et al 1993;Lew et al 1999;Salvatore et al 2000). This serine residue is phosphorylated in vitro by cAMP-dependent kinase (PKA), protein kinase C (PKC), mitogen-activated protein kinase-activated protein kinase 1 (MAPKAP-K1) and Ca 2+ /calmodulin-dependent protein kinase II (CaM-KII; Kappock and Caradonna 1996).…”
mentioning
confidence: 99%